2011
DOI: 10.1371/journal.pone.0018486
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Clinical-Radiographic Score to Assess the Probability of Pulmonary Tuberculosis in Suspect Patients with Negative Sputum Smears

Abstract: BackgroundClinical suspects of pulmonary tuberculosis in which the sputum smears are negative for acid fast bacilli represent a diagnostic challenge in resource constrained settings. Our objective was to validate an existing clinical-radiographic score that assessed the probability of smear-negative pulmonary tuberculosis (SNPT) in high incidence settings in Peru.Methodology/Principal FindingsWe included in two referral hospitals in Lima patients with clinical suspicion of pulmonary tuberculosis and two or mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…After full-text review, 174 articles were excluded for various reasons and 13 articles (all observational studies) were included in the systematic review ( fig. 1) [20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After full-text review, 174 articles were excluded for various reasons and 13 articles (all observational studies) were included in the systematic review ( fig. 1) [20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Resultsmentioning
confidence: 99%
“…Studies that only included patients with possible PTB who were found to be sputum smear negative We identified five studies in this category [26][27][28][29][30]. Four studies were conducted in an inpatient setting for the purpose of determining a clinical rule for respiratory isolation [26,27,29,30]; while one study was performed in an outpatient setting [28] (table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations